On the issue of transformational management at the Agency for Civil Service Affairs in the course of a new remuneration system piloting - Amirova, А.К. (BUKETOV BUSINESS REVIEW, 2020)
Object: is to analyze transformation processes and organizational aspects of the Agency for Civil Service Affairs (hereinafter – the Agency) to determine the guidelines for further improvement of its activities. Methods: a method of organizational diagnosis, which involves analysis of Strategic plan and organizational structure of the Agency in a prism of foreign experience, description of life cycle, survey of employees as well as the cost-effectiveness analysis of the pilot project in the Agency. Findings: it was found that (i) despite the direct relationship between bonus payments (or rather the size of the bonus fund) and performance indicators, there is a deterioration in individual indicators. At the same time, the bonus fund has not been adjusted; (ii) the Agency's mission and vision need to be refined in terms of concretization and compliance with the guidelines of the country's strategic documents; (iii) there is a lack of competence, which requires a single state body that will comprehensively address pressing issues of the public administration system; (iv) improvement of business processes in the Agency by taking into account the proposals of respondents. Conclusions: taking into account the comprehensive diagnostics, the author developed proposals that are aimed not only at improving the Agency's performance, but also at launching systemic changes in the public sector.